Pengaruh Model Pembelajaran Project Based Learning terhadap Literasi Matematika pada Siswa Kelas Tinggi SDN Tamanarum 1 - Khusnul Fatimah Nurjianti Hamidah; Hartini Hartini; Ivayuni Listiani (Universitas PGRI Madiun, 2022)
Currently, mathematical literacy is needed by students to develop their knowledge and potential and to meet the requirements in the independent curriculum. The purpose of this study was to determine the effect of the Project Based Learning model on mathematical literacy skills in high- grade students, with experimental quantitative methods in finding the effect of variables with certain treatments, namely using the application of Project Based Learning (PjBL) on mathematical literacy skills. The design of this study is pra-experiment with one group pretest-posttest design. The subjects of this study were high-grade students, totaling 30 students and concluded that the Project Based Learning model is able to improve the mathematical literacy skills of high-grade students. This is evidenced by calculations on the t-test with the result of 0,000 < sign. 0,05 in class IV, V, and VI. In addition, there is also an increase in the average score on the result of the pretest and posttest. The increase that occurred in grade IV was 27, grade V as much as 26,66, and in grade VI by 28,04.